ANALISIS PERAN ORANG TUA TERHADAP KEBERSIHANGIGI DAN MULUT ANAK DI TK SULTAN AGUNG 02 SEMARANG - Eki Novitasari; Anita Chandra Dewi; Ratna Wahyu Pusari (STKIP Subang, 2023)
The role of parents is very important in the oral hygiene of young children. This study aims to describe the role of parents in maintaining children's oral and dental hygiene at TK Sultan Agung 02 Semarang. This research is qualitative with a descriptive approach. The method used in this research is a descriptive qualitative method. The researcher's target was 13 subjects from a total of 34 students in Kindergarten B aged 5-6 years. Data collection techniques use observation, questionnaires, interviews and documentation. The results of this study show that maintaining oral hygiene starts from an early age, so it is necessary to accompany parents in caring for children's dental and oral hygiene. This was seen from the beginning of the researcher's observations of students, who saw that children really liked sweet foods such as chocolate. , yupy, etc., interviews conducted by researchers with students, as well as the results of questionnaires with parents, students really like sweet foods, as a result the condition of children's teeth, some have cavities, grouped teeth, and dental caries, so the role of people is very necessary. parents on children's oral and dental hygiene.